Locus of Control Mediates the Effect of Financial Behavior and Social Trust on Sharia-Compliant Investment Decisions - Achmad Hasan Hafidzi; Elok Sri Utami; Hadi Paramu; Ibna Kamilia Fiel Afroh; Norita Citra Yuliarti (The Indonesian Accounting Review, 2025)
This study aims to analyze the role of locus of control in mediating the effect of financial behavior and social trust on Sharia-compliant investment decisions among investors in East Java. This study uses a quantitative approach involving 532 respondents. Data are analyzed using Structural Equation Modeling (SEM). The results of this study show that locus of control significantly mediates the effect of financial behavior and social trust on Sharia-compliant investment decisions. Interestingly, financial behavior has a direct negative effect on investment decisions, but this effect changes to positive when mediated by locus of control. This study strengthens the integration of Social Cognitive Theory, Locus of Control Theory, and Theory of Planned Behavior in the context of Sharia finance, thus providing a comprehensive understanding of how internal beliefs influence investment actions. Practically, these findings suggest that financial literacy programs should include a psychological empowerment approach, especially strengthening people’s beliefs about their control and ability to manage investments. The novelty of this study is the use of locus of control as an intervening variable in the study of sharia-compliant investment at the regional level.